Ethical AI in Accounting and Finance: Risks and Opportunities for Business Strategy: Risks and Opportunities for Business Strategy - Moh Syifauddin; Rita Yuliana; Romadlani, M Masqatul Imam (International Economic Conference of Business and Accounting, 2025)
Abstract Artificial Intelligence (AI) is increasingly applied in accounting and finance to improve efficiency, accuracy, and decision-making. While offering significant strategic opportunities, its adoption also raises critical ethical challenges such as algorithmic bias, data privacy risks, transparency issues, and accountability concerns. These challenges influence business strategy by requiring firms to balance technological innovation with ethical responsibility to maintain trust and competitiveness. This paper examines the risks and opportunities of ethical AI in accounting and finance from a strategic perspective. Drawing on literature and case insights, the discussion highlights how organizations can minimize risks through governance and ethical frameworks while leveraging AI to enhance fraud detection, compliance, and strategic advantage. The analysis suggests that embedding ethics into AI adoption is not merely a regulatory requirement but a strategic imperative to ensure sustainable business value. The paper concludes with recommendations for aligning ethical AI with business strategy. Keywords: Ethical AI, Accounting, Finance, Business Strategy, Risk and Opportunity